2008
DOI: 10.1364/oe.16.018976
|View full text |Cite
|
Sign up to set email alerts
|

Generation of large alkali vapor densities inside bare hollow-core photonic band-gap fibers

Abstract: We demonstrate the ability to generate extremely large rubidium densities in uncoated hollow-core photonic band-gap fibers using light-induced atomic desorption. Once the fiber is exposed to Rb vapor for 1-2 weeks, and this atomic source is removed, the fiber yields large desorbable densities for an extended period of time. We show that optical depths greater than e(-1200) can be created within seconds. Our observed Rb densities are several orders of magnitude larger than any previously reported to be generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…LIAD was also observed from the core of hollow photonic fibers, as reported in [44][45][46][47][48][49][50][51], just to name a few.…”
Section: Liad In Other Dielectric Mediamentioning
confidence: 53%
“…LIAD was also observed from the core of hollow photonic fibers, as reported in [44][45][46][47][48][49][50][51], just to name a few.…”
Section: Liad In Other Dielectric Mediamentioning
confidence: 53%
“…And the optical coupling efficiency of this system can be improved significantly comparing with the traditional configuration. Slepkov et al also demonstrated the possibility of introducing alkali vapor into a standard hollow-core fiber with sufficient gas density [8] . Recently, Sintov et al calculated the physical features of a rubidium vapor-based fiber laser using a simple mathematical model, in which the HC-PCF-DPAL was treated as a three-level laser system [9] .…”
Section: Introductionmentioning
confidence: 99%
“…We fit the probe absorption data to a Voigt profile (red curve) which takes into account both the homogenous (Lorentzian) and inhomogenously Doppler broadened (Gaussian) line shapes. Since the Rb atoms are confined to a 6-µm core, the interaction time with the optical mode is limited to the time it takes for the atoms to move across the beam and leads to transit-time broadening of the absorption lines, which we take into account while simulating the Voigt function [22,26]. The temperature of the Rb atoms inside the core is inferred to be T ∼ 500 K from the Voigt function fit in Fig 2(a)-(b).…”
mentioning
confidence: 99%
“…The temperature of the Rb atoms inside the core is inferred to be T ∼ 500 K from the Voigt function fit in Fig 2(a)-(b). The higher temperature of the atoms (500 K) as compared to the chamber temperature of 373 K appears to be a result of the high kinetic energy of the released atoms [26] which also results in the increased Doppler broadening of the Rb transition lines. We also note that the large OD's are only generated when the vapor generation beam is coupled into the fiber core.…”
mentioning
confidence: 99%